The Role of Enlightened Leadership in the Face of Career Alienation: An Applied Study at Tikrit University - Mizhir Abdullah Ahmed; Ibraheem Mohammed Saleh; Firas Hesan Rasheed (Research Parks Publishers, 2023)
Purpose – The study aimed to learn about the role of enlightened leadership in the face of career alienation by applying to the University of Tikrit. Design/methodology/approach – Using the analytical descriptive curriculum researcher to describe and analyze the opinions of the individuals of the sample and test the impact relationships between the research variables, representing the study community of Tikrit University through a random sample based on (82) Eighty-two teaching staff at Tikrit University Colleges, and the researcher also used a package of statistical programmes for social sciences known as